2015
DOI: 10.1016/j.forsciint.2015.07.035
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between atmospheric/humidity and vacuum cyanoacrylate fuming of latent fingermarks

Abstract: A number of pseudo-operational trials were set up to compare the atmospheric/humidity and vacuum cyanoacrylate fuming processes on plastic carrier bags. The fuming processes were compared using two-step cyanoacrylate fuming with basic yellow 40 (BY40) staining and a one-step fluorescent cyanoacrylate fuming, Lumicyano 4%. Preliminary work using planted fingermarks and split depletions were performed to identify the optimum vacuum fuming conditions. The first pseudo-operational trial compared the different fumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Two runs were carried out to evaluate Lumicyano™ fluorescence stability (cabinet and LumiFume™) and assessed over a period of days up to a total 28 days. Fluorescence observations were strong after 28 days reflecting previous studies [11,12,14,15]; however, the 10% Lumicyano™ concentration allows for a higher dye concentration providing more time for visualisation before the complete decay of fluorescence (figure 8). Fingermarks developed on glass slides in the cabinet were noted to feature overdeveloped marks (figure 9); however, no overdeveloped marks were observed with the LumiFume™ device which addresses a concern of previous studies that being unable to monitor the mark development (due to the tent) may lead to unintended overdeveloped marks [22].…”
Section: Evaluation Of the Stability Of Lumicyano™ Fluorescencesupporting
confidence: 79%
See 1 more Smart Citation
“…Two runs were carried out to evaluate Lumicyano™ fluorescence stability (cabinet and LumiFume™) and assessed over a period of days up to a total 28 days. Fluorescence observations were strong after 28 days reflecting previous studies [11,12,14,15]; however, the 10% Lumicyano™ concentration allows for a higher dye concentration providing more time for visualisation before the complete decay of fluorescence (figure 8). Fingermarks developed on glass slides in the cabinet were noted to feature overdeveloped marks (figure 9); however, no overdeveloped marks were observed with the LumiFume™ device which addresses a concern of previous studies that being unable to monitor the mark development (due to the tent) may lead to unintended overdeveloped marks [22].…”
Section: Evaluation Of the Stability Of Lumicyano™ Fluorescencesupporting
confidence: 79%
“…This is typically done with powdering or a fluorescent stain such as basic yellow 40 (BY40) and Rhodamine 6G. Over the last decade, investigations and comparisons with one-step fluorescent cyanoacrylates, Lumicyano™, PolyCyano, CN Yellow and PECA Multiband, have taken place [10][11][12][13][14][15][16][17]. One-step cyanoacrylates feature cyanoacrylates with a fluorescent dye or fluorophore conjugated to the glue [18].…”
Section: One-step Fluorescent Cyanoacrylate Processmentioning
confidence: 99%
“…Farrugia performed a comparative study on metallized plastic films, to find out the effect of cyanoacrylate fuming under vacuum. This method is performed in a fuming cabinet.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Farrugia et al (2015) suggested the use of atmospheric/humidity fuming process over vacuum fuming process for both two-step and one-step cyanoacrylate fuming for developing latent fingermarks on plastic carrier bags. They also compared two-step cyanoacrylate fuming using basic yellow 40 (LCA4% → LCA4% → BY40) and a one-step fluorescent cyanoacrylate fuming using Lumicyano and observed that two-step process gave better quality prints than one-step process under vacuum conditions.…”
Section: Evaluation Of Cyanoacrylate Fuming Methodsmentioning
confidence: 99%